2017
DOI: 10.1103/physrevc.95.034603
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic cluster model for the description of new experimental results on the C13(O18,O

Abstract: The 13 C(18 O , 16 O) 15 C reaction is studied at 84 MeV incident energy. Excitation energy spectra and absolute cross-section angular distributions for the strongest transitions are measured with good energy and angular resolutions. Strong selectivity for two-neutron configurations in the states of the residual nucleus is found. The measured cross-section angular distributions are analyzed by exact finite-range coupled reaction channel calculations. The two-particle wave functions are extracted using the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 55 publications
3
33
0
Order By: Relevance
“…The spectroscopic amplitudes for both target and projectile overlaps are usually set equal to 1.0 in this model. In a recent work it was shown [41] that a microscopic cluster calculation can be performed if the two-neutron spectroscopic amplitudes from extended shell model calculations are used. A unitary transformation allows one to derive the spectroscopic amplitudes of the cluster model, and the parallel and antiparallel configuration of the two neutrons inside the cluster can then be considered.…”
Section: Crc and Dwba Calculations Results And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectroscopic amplitudes for both target and projectile overlaps are usually set equal to 1.0 in this model. In a recent work it was shown [41] that a microscopic cluster calculation can be performed if the two-neutron spectroscopic amplitudes from extended shell model calculations are used. A unitary transformation allows one to derive the spectroscopic amplitudes of the cluster model, and the parallel and antiparallel configuration of the two neutrons inside the cluster can then be considered.…”
Section: Crc and Dwba Calculations Results And Discussionmentioning
confidence: 99%
“…This model space allowed one to describe the experimental energy spectra of 64 The spectroscopic amplitudes for the projectile overlaps were taken from Ref. [41], where it was shown that the zbm interaction [47] is suitable for describing both energy spectra of carbon and oxygen isotopes as well as neutron transfer reactions. The obtained results are compared with the experimental data in Fig.…”
Section: B Shell-model Calculationsmentioning
confidence: 99%
“…A fundamental relevance for the Project has the INFN facility at Laboratori Nazionali del Sud (LNS) in Catania, made by the Superconducting Cyclotron for the acceleration of the required high resolution and low emittance heavy-ion beams and the MAGNEX large acceptance magnetic spectrometer for the detection of the ejectiles [9]. Thanks to the application of the powerful trajectory reconstruction technique [11] MAGNEX guarantees high energy, mass and angle resolutions, which established its relevance in the heavy-ion physics research [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A key aspect of the project is the use at Laboratori Nazionali del Sud (LNS) in Catania of the Superconducting Cyclotron for the acceleration of the required high resolution and low emittance heavy-ion beams and the MAGNEX large acceptance magnetic spectrometer for the detection of the ejectiles [10]. Thanks to the application of the powerful trajectory reconstruction technique [11] MAGNEX guarantees high energy, mass and angle resolutions, which established its relevance in the heavy-ion physics research [12][13][14][15]. The concurrent measurement of the other relevant reaction channels allows to isolate the direct DCE mechanism from the competing multi-nucleon transfer processes.…”
Section: Introductionmentioning
confidence: 99%